2021
DOI: 10.1016/j.jiph.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hematologic presentations of adults with COVID-19 patients in Jeddah: A case control study

Abstract: Background Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2), is associated with significant morbidity and mortality. The clinical features of COVID-19 were mentioned in previous studies. However, risk factors for COVID-19 are not fully recognized. The aim of this study is to characterize risk factors and clinical features of COVID-19 disease in Jeddah, Saudi Arabia. Methods A retrospective, chart-review, case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
6
5
0
Order By: Relevance
“…Another study from Oman showed that the mean age of the 63 patients was 48 years [ 22 ]. Most of our patients were men, which is consistent with previous studies [ 19 , 20 , 23 ]. This suggests that SARS-COV-2 is more likely to infect males, as sex hormones in females may play a protective role in fighting viral infections via innate and adaptive immunity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another study from Oman showed that the mean age of the 63 patients was 48 years [ 22 ]. Most of our patients were men, which is consistent with previous studies [ 19 , 20 , 23 ]. This suggests that SARS-COV-2 is more likely to infect males, as sex hormones in females may play a protective role in fighting viral infections via innate and adaptive immunity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that SARS-COV-2 is more likely to infect males, as sex hormones in females may play a protective role in fighting viral infections via innate and adaptive immunity [ 24 ]. The most common comorbidities were diabetes mellitus and hypertension in COVID-19 patients, a similar finding to previous studies [ 23 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…This may be because regular administration of anticoagulant drugs for treatment in severe patients decreased the levels of D-dimers in patients presumably. Similar results were obtained in studies conducted to assess on-protocol COVID-19 patients (Kamel et al, 2021;Tassiopoulos et al 2021). Apparently, due to similar reasons, the D-dimer had a highly positive significant correlation with WBC, INR, procalcitonin, and LDH.…”
Section: Laboratory Parameterssupporting
confidence: 81%
“…This may be because the regular administration of anticoagulant drugs for treatment in severe patients decreased the levels of D-dimers in them presumably (Mouhat et al, 2020). Similar results were obtained in studies conducted to assess on-protocol COVID-19 patients (Kamel et al, 2021;Tassiopoulos et al, 2021). Apparently, due to similar reasons, the D-dimer had a highly significant positive correlation with WBC, INR, procalcitonin, and LDH.…”
Section: Laboratory Parameterssupporting
confidence: 72%